2019
DOI: 10.1128/aac.00448-19
|View full text |Cite
|
Sign up to set email alerts
|

20S Proteasome as a Drug Target in Trichomonas vaginalis

Abstract: Trichomoniasis is a sexually transmitted disease with hundreds of millions of annual cases worldwide. Approved treatment options are limited to two related nitro-heterocyclic compounds, yet resistance to these drugs is an increasing concern. New antimicrobials against the causative agent, Trichomonas vaginalis, are urgently needed. We show here that clinically approved anticancer drugs that inhibit the proteasome, a large protease complex with a critical role in degrading intracellular proteins in eukaryotes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 63 publications
(68 reference statements)
2
22
0
Order By: Relevance
“…Moreover, the study showed that incorporating a d-amino acid at the P3 position can significantly modulate host cytotoxicity without interfering significantly with anti-plasmodial activity [61]. In another study, a carmaphycin-related synthetic analogue, carmaphycin-17 (18, Figure 3), was found to have greater inhibitory activity against Trichomonas vaginalis than the reference drug metronidazole [62]. Trichomonas vaginalis is the causative agent of the sexually transmitted disease, trichomoniasis.…”
Section: Protease Enzymesmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the study showed that incorporating a d-amino acid at the P3 position can significantly modulate host cytotoxicity without interfering significantly with anti-plasmodial activity [61]. In another study, a carmaphycin-related synthetic analogue, carmaphycin-17 (18, Figure 3), was found to have greater inhibitory activity against Trichomonas vaginalis than the reference drug metronidazole [62]. Trichomonas vaginalis is the causative agent of the sexually transmitted disease, trichomoniasis.…”
Section: Protease Enzymesmentioning
confidence: 98%
“…Trichomonas vaginalis is the causative agent of the sexually transmitted disease, trichomoniasis. In addition, 18 was found to be selective for T. vaginalis due to its increased potency against the β1 and β5 catalytic subunits of the T. vaginalis proteasome as compared to the human proteasome subunits [62]. Compound 18 is also shown to be selective for the Schistosoma mansoni proteasome (about 13.2fold more potent) over the human proteasome [63].…”
Section: Carmaphycinsmentioning
confidence: 99%
“…Will inhibition of the virulence enzyme protect males against trichomoniasis? O'Donoghue, Bibo-Verdugo [16] showed that clinically approved cancer drugs that inhibit the proteasome also have high activity in the enriched T. vaginalis in cell-free assays. The proteasome inhibitor carmaphycin-17 ( Fig.…”
Section: Mechanisms Of Anti-trichomonad Effectsmentioning
confidence: 99%
“…That said, new therapies are urgently needed given the lack of effective vaccines, drug resistance, limited efficacy, and toxicity associated with current treatment [4][5][6]. Given that the UPS pathway is essential for cell survival, inhibition of the proteasome has emerged as an attractive anti-parasitic target [7][8][9][10][11][12][13]. However, the regulation of UPS-mediated protein degradation in clinically important protozoans remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%